Variation of aerobic performance indices of professional elite soccer players during the annual macrocycle - Bekris, E.; Mylonis, E.; Gissis, I.; Katis, A.; Metaxas, T.; Komsis, S.; Kompodieta, N. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: The purpose of the present study was to examine the variation of aerobic performance parameters of elite Greek soccer players. METHODS: In the study participated twenty-four (24) male professional soccer players (age: 24.3±4.3 years, height: 180.3±3.8 cm and mass: 77.4±6.1 kg), who competed at the top level of the Greek National Championship. Four measurements regarding aerobic parameters were conducted during the annual training cycle (preseason, start of the season, end of the first championship round and end of the season). RESULTS: The ANOVA analysis showed that maximum oxygen uptake (VO2max) was significantly increased after the completion of the preseason and continued to increase until the end of the first round of the Championship. In contrast, a decline was observed towards the end of the season. The velocity to maximum oxygen uptake (vVO2max) and the velocity parameter in respiratory threshold were significantly increased at the end of the preseason and the end of the first round, while the parameters were differentiated at the end of the season. The lactate concentration showed no significant changes during the four measurements. CONCLUSIONS: A systematic observation of players` performance, especially recording parameters such as VO2max, during the annual training cycle, could provide the necessary feedback for both trainers and players in order to increase team performance.